Elevated NT-proBNP predicts unfavorable outcomes in patients with acute ischemic stroke after thrombolytic therapy - Zhuang Zhu; Bilal Muhammad; Bo Du; Ning Gu; Tian-Yue Meng; Shu Kan; Ying-Feng Mu; Yan-Bo Cheng; Shi-Guang Zhu; De-Qin Geng (BMC Neurology, 2023)
Abstract Objective Few studies correlated n-terminal pro-brain natriuretic peptide (NT-proBNP) with early neurological deterioration (END) and prognosis of acute ischaemic stroke (AIS) patients with rt-PA intravenous thrombolysis. Therefore this study aimed to investigate the relationship between NT-proBNP and END, and prognosis after intravenous thrombolysis in patients with AIS. Methods A total of 325 patients with AIS were enrolled. We performed the natural logarithm transformation on the NT-proBNP [ln(NT-proBNP)]. Univariate and multivariate logistic regression analyses were performed to assess the relationship between ln(NT-proBNP) and END, and prognosis and receiver operating characteristic (ROC) curves were used to show the sensitivity and specificity of NT-proBNP. Results After thrombolysis, among 325 patients with AIS, 43 patients (13.2%) developed END. In addition, three months follow-up showed a poor prognosis in 98 cases (30.2%) and a good prognosis in 227 cases (69.8%). Multivariate logistic regression analysis showed that ln(NT-proBNP) was an independent risk factor for END (OR = 1.450,95%CI:1.072 ~ 1.963, P = 0.016) and poor prognosis at three months follow-up (OR = 1.767, 95%CI: 1.347 ~ 2.317, P < 0.001) respectively. According to ROC curve analysis, ln(NT-proBNP) (AUC 0.735, 95%CI: 0.674 ~0.796, P < 0.001) had a good predictive value for poor prognosis, with a predictive value of 5.12 and sensitivity and specificity of 79.59% and 60.35% respectively. When combined with NIHSS to predict END(AUC 0.718, 95%CI: 0.631 ~ 0.805, P < 0.001) and poor prognosis(AUC 0.780, 95%CI: 0.724 ~ 0.836, P < 0.001), the predictive value of the model is further improved. Conclusion NT-proBNP is independently associated with END and poor prognosis in patients with AIS following intravenous thrombolysis and has a particular predictive value for END and poor prognosis.